Thyroid Disorders in Polycystic Ovarian Syndrome and It’s Association with Clinical and Biochemical Parameters - Sumona, Rezwana Haque; Haque, Nadira; Hosain, Nazmul; Ara, Begum Hosne; Parvin, Nilufa; Debnath, Keya; Akter, Ruma (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Poly-Cystic Ovarian Syndrome (PCOS) is a common endocrine disorder which causes anovulatory female infertility. Thyroid dysfunction can lead to subtle change in ovulation and endometrial receptivity which may have profound effect on fertility. Objective of the study is to evaluate thyroid function in woman with PCOS to find out the frequency of thyroid disorders using TSH, FT3, FT4 in PCOS patients and to see association of altered thyroid function with clinical, hormonal and ultrasonogram features. Materials and methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Institute of Child and Mother Health (ICMH) Dhaka and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between May 2018 and February 2019. A total of 100 patients in reproductive age group (Aged between 20 and 40 years) attending theOutpatient Department (OPD) who were diagnosed as PCOS were included in this study. Among them 21 PCOS with normal thyroid function was considered as group I and 79 PCOS with abnormal thyroid function was considered as group II.All the cases of PCOS were subjected to investigations like FSH, LH, Serum Prolactin, TSH, Free T3, Free T4. Results: A total of 100 patients were included in this study. It was found that 3/4 patients had euthyroid and 18% had subclinical hypothyroidism, 86% patients were Oligomenorrhea, 70% had primary sub fertility, 53% had hirsutism, 25% had secondary sub fertility. Conclusion: Most of the Polycystic ovary syndrome patients belonged to age between 25 and 30 years. Oligomenorrhea, primary subfertility and hirsutism are the most common presenting complains. Hypothyroidism found in 20.0% of the women with PCOS. JCMCTA 2023 ; 34 (1) : 121-126